Optimization of high fiber yogurt drinks with sala mango peel powder (Hiyo) using Response Surface Methodology (RSM) - Ernie Faridah Mat Nordin (School of Bioprocess Engineering, University Malaysia Perlis, 2011)
Response Surface Methodology (RSM) was employed to investigate the combined effects of plain yogurt, skim milk and mango peel powder on the hardness of high fiber yogurt drink. The second-order polynomial model was fitted to the hardness of runs as the response. Lack-of-fit tests were not significant and determination coefficients (R2) were 95.99%. Mango peel powder was supplement into yogurt drink at different level (10%, 20% and 30%). The optimum amount of ingredients in producing high fiber of yogurt drink shown 71.38 g of plain yogurt, 10.85g of skim milk and 11.12 g of mango peel powder were selected by Response Surface Method (RSM) to achieve the hardness of high fiber yogurt drink, which is the ranged in overall acceptability from 83 to 136 g. The texture profile analysis evaluated by texture analyzer (Brookfield). Supplementation of mango peel powder in producing high fiber yogurt drink was shown to increase the hardness, gumminess and chewiness parameters. The physico-chemical characteristics of the supplemented and control yogurt drink was determined. Result indicated that addition of mango peel powder significantly decreased the moisture content (75.16 %) respectively as compared to the control yogurt drink (86.95 %). However, the crude fiber (2.70 %), protein (1.02 %), ash (0.59 %) and carbohydrate (19.74 %) increased significantly (p<0.05). The control yogurt drink has fat content decreased from 1.06 % to 0.79 % for yogurt drink supplemented with mango peel powder.